`sum_(n=1)^oo n*e^(-n/2)` Confirm that the Integral Test can be applied to the series. Then use the Integral Test to determine the convergence or divergence of the series.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Integral test is applicable if `f ` is positive and decreasing function on interval `[k,oo)` where `a_n = f(x).`  

If `int_k^oo f(x) dx` is convergent then the series `sum_(n=k)^oo a_n` is also convergent.

If `int_k^oo f(x) dx` is divergent then the series `sum_(n=k)^oo a_n` is also divergent.

For the  series `sum_(n=1)^oo n*e^(-n/2)` , we have `a_n =n*e^(-n/2) ` then we may let the function:

`f(x) =x*e^(-x/2)` .

 The graph of f(x) is:

 As shown on the graph, `f(x)` is positive on the interval `[1,oo)` .  Based on the behavior of the graph as x increases, the function eventually decreases. We can confirm this by applying First Derivative test.  To determine the derivative of the function, we may apply the Product rule for differentiation:` d/(dx) (u*v)= v* du+ u *dv` .

Let: `u =x` then `du = 1`

       `v=e^(-x/2)`  then `dv =- e^(-x/2)/2`

Note:  `d/(dx)e^(-x/2) = e^(-x/2) * d/(dx) (-x/2)`

                      ` =e^(-x/2) *(-1/2)`

                      ` =- e^(-x/2)/2`

Applying the Product rule for differentiation, we get:

`f'(x) =e^(-x/2) * 1 + x *- e^(-x/2)/2`

         `=e^(-x/2) - (xe^(-x/2))/2`

         `= (e^(-x/2) (2-x))/2`

Solve for critical values of `x` by applying `f'(x) =0` .

`(e^(-x/2) (2-x))/2 =0`

` (e^(-x/2) (2-x))=0`

 Apply zero-factor property:

`(2-x)=0` then `x=2`

Using test point `x=5 ` after `x=2` , we get:

`f'(5) = (e^(-5/2) (2-5))/2 ~~ -0.12313` .

When `f'(x) lt0` , then the function is decreasing for the given integral.

Then `f(x)=x*e^(-x/2)` from the interval `[2, oo)` . Since the function is ultimately decreasing on the interval `[1,oo)` we may apply the integral test:

`int_1^oo x*e^(-x/2) dx= lim_(n-gtoo) int_1^tx*e^(-x/2)dx`

To determine the indefinite integral of `int_1^t x*e^(-x/2)dx` , we may apply u-substitution by letting: ` u =-x/2` or `x=-2u ` then `du = -1/2 dx` or `-2du =dx` .

The integral becomes:

`int x*e^(-x/2)dx=int (-2u)*e^u*(-2du)`

                     ` = int 4ue^u du`

                     ` = 4 int ue^udu`

Apply the integration formula for exponential functions: `int xe^xdx=(x-1)e^x+C.`

`4 int ue^udu=4 *(u-1)e^u`

                     `= 4ue^u -4e^u`

Plug-in `u =-x/2` on `4ue^u -4e^u` , we get:

`int_1^t x*e^(-x/2)dx =4(-x/2)e^(-x/2) -4e^(-x/2)|_1^t`

                     `=-2xe^(-x/2) -4e^(-x/2)|_1^t`

Applying definite integral formula: `F(x)|_a^b = F(b)-F(a).`

`-2e^(-x/2) -4e^(-x/2)|_1^t=[-2te^(-t/2) -4e^(-t/2)]-[-2*1e^(-1/2) -4e^(-1/2)]`

                             `=-2te^(-t/2) -4e^(-t/2)+2e^(-1/2) +4e^(-1/2)`

                             `=-2te^(-t/2) -4e^(-t/2)+6e^(-1/2)`

Applying `int_1^t x*e^(-x/2)dx =-2te^(-t/2) -4e^(-t/2)+6e^(-1/2)` , we get:

`lim_(n-gtoo) int_1^tx*e^(-x/2)dx =lim_(n-gtoo)[-2te^(-t/2) -4e^(-t/2)+6e^(-1/2)]`

                              `=lim_(n-gtoo)-2te^(-t/2) -lim_(n-gtoo)4e^(-t/2)+lim_(n-gtoo)6e^(-1/2)`

                             ` =-2*ooe^(-oo) -4e^(-oo)+6e^(-1/2)`


                            `=6/e^(1/2)` or `6/sqrt(e)`

The  `lim_(n-gtoo) int_1^tx*e^(-x/2)dx =6/sqrt(e)` implies that the integral converges.


The integral `int_1^oo x*e^(-x/2)dx` is convergent therefore the series `sum_(n=1)^oo n*e^(-n/2) ` must also be convergent.

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial